STUDY ON THE EFFECT OF THE DRUG FS-1 ON ACTIVITY OF BACTERIAL ANTIOXIDANT SYSTEM - B.F. Kerimzhanova; S.S. Kassymbekova; N.B. Akhmatullina; Zh.A. Iskakbayeva; E.N. Sakhipov; A.I. Ilin (Academic Scientific Journal of Chemistry, 2019)
The effect of iodine-containing complex FS-1 on the antioxidant system in M. smegmatis is described. It is shown that FS-1 under in vitro experimental conditions at doses of 2 μg/ml and 4 μg/ml inhibits the functional activity of bacterial superoxide dismutase enzyme on the example of atypical mycobacteria M. smegmatis, i.e. resistance to oxidative stress.